Tagging of multimedia flows for active queue management - Wu, Jionghui. (2008)
Due to tremendous increase of traffic in Internet, congestion has become a major problem in today's Internet that has resulted in excessive packet drops and delays in the network. Many queue managements such as Tail Drop, Front Drop, Random Drop and Random Early Detection (RED) have been proposed to control congestion. However, such queue managements are suitable where traffic sources have same priority and Quality of Service (QoS) requirement. Therefore, these schemes are not effective for multimedia flows. Multimedia flows have different bandwidth, delay and loss requirements. Text and image traffics are predominantly burst-type and they require reliable service from the network, but they can tolerate delay. In contrast, audio and video traffics are stream oriented, whereby a stream is a continuous flow of information that has to be delivered in a timely fashion where error can be tolerated. Therefore, it is desirable to propose an approach that ensures isolation of service class while allowing sharing of buffer space.